Microscopic observations reveal that fusogenic peptides induce liposome shrinkage prior to membrane fusion - Nomura, Fumimasa (National Academy of Sciences, 2004)
To study the mechanisms involved in membrane fusion, we visualized the fusion process of giant liposomes in real time by optical dark-field microscopy. To induce membrane fusion, we used (i) influenza hemagglutinin peptide (HA), a 20-aa peptide derived from the N-terminal fusion peptide region of the HA2 subunit, and (ii) two synthetic analogue peptides of HA, a negatively (E5) and positively (K5) charged analogue. We were able to visualize membrane fusion caused by E5 or by K5 alone, as well as by the mixture of these two peptides. The HA peptide however, did not induce membrane fusion, even at an acidic pH, which has been described as the optimal condition for the fusion of large unilamellar vesicles. Surprisingly, before membrane fusion, the shrinkage of liposomes was always observed. Our results suggest that a perturbation of lipid bilayers, which probably resulted from alterations in the bending folds of membranes, is a critical factor in fusion efficiency.